The environment a history of an idea - Warde, Paul ca. 20./21. Jh; Robin, Libby 1956-; Sörlin, Sverker 1956- (John Hopkins University Press, 2021)
"The idea of "the environment" was a planet-changing idea, making the planet visible in a wholly new way. The Environment: A History tells the story of the emergence of this idea. It is an intellectual and scientific history of the idea of the environment as a centripetal force in historical debates about climate change and the fate of the planet. According to the authors, our contemporary notion of the environment as a planet-wide web of interconnection and consequence of which the natural world is a part was forged by post-World War scientific experts. This book is about the imagination, the history, and the creativity of these experts, as well as their technical and diplomatic skills, and how well ordinary people have understood these and contributed to framing environmental concerns. The environment provided a concept that linked changes close to home to world-wide pressures. And in creating an object of imagination and measurement, it allowed new kinds of questions about nature and human responsibilities to be asked. Is the world sick? Is the Environment getting worse or better? In addition to creating a particular way of looking at our world it also created a movement and various kinds of knowledge and expertise"...
Keywords: Ideengeschichte; SCIENCE / History / bisacsh; SCIENCE / Life Sciences / Ecology / bisacsh; Environmental sciences -- Philosophy; Human ecology; Nature -- Effect of human beings on; SCIENCE / History; SCIENCE / Life Sciences / Ecology; Ökologie; Umwelt; Umweltschutz